Long-distance effects of site-directed mutations on backbone conformation in bacteriorhodopsin from solid state NMR of [1-13C]Val-labeled proteins. - Tanio, M (1999)
We have recorded 13C cross-polarization-magic angle spinning and dipolar decoupled-magic angle spinning NMR spectra of [1-13C]Val-labeled wild-type bacteriorhodopsin (bR), and the V49A, V199A, T46V, T46V/V49A, D96N, and D85N mutants, in order to study conformational changes of the backbone caused by site-directed mutations along the extracellular surface and the cytoplasmic half channel. On the basis of spectral changes in the V49A and V199A mutants, and upon specific cleavage by chymotrypsin, we assigned the three well-resolved 13C signals observed at 172.93, 172.00, and 171. 11 ppm to [1-13C]Val 69, Val 49, and Val 199, respectively. The local conformations of the backbone at these residues are revealed by the conformation-dependent 13C chemical shifts. We find that at the ambient temperature of these measurements Val 69 is not in a beta-sheet, in spite of previous observations by electron microscopy and x-ray diffraction at cryogenic temperatures, but in a flexible turn structure that undergoes conformational fluctuation. Results with the T46V mutant suggest that there is a long-distance effect on backbone conformation between Thr 46 and Val 49. From the spectra of the D85N and E204Q mutants there also appears to be coupling between Val 49 and Asp 85 and between Asp 85 and Glu 204, respectively. In addition, the T2 measurement indicates conformational interaction between Asp 96 and extracellular surface. The protonation of Asp 85 in the photocycle therefore might induce changes in conformation or dynamics, or both, throughout the protein, from the extracellular surface to the side chain of Asp 96.